2013
DOI: 10.1371/journal.pone.0060192
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Risk amongst Nursing Home Residents Evacuated after the Fukushima Nuclear Accident: A Retrospective Cohort Study

Abstract: BackgroundSafety of evacuation is of paramount importance in disaster planning for elderly people; however, little effort has been made to investigate evacuation-related mortality risks. After the Fukushima Daiichi Nuclear Plant accident we conducted a retrospective cohort survival survey of elderly evacuees.MethodsA total of 715 residents admitted to five nursing homes in Minamisoma city, Fukushima Prefecture in the five years before 11th March 2011 joined this retrospective cohort study. Demographic and clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
103
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 106 publications
(105 citation statements)
references
References 20 publications
2
103
0
Order By: Relevance
“…In three of 5 facilities, initial evacuation significantly elevated mortality after the disaster 3) . Results of previous studies 1,3) are consistent with our data.…”
Section: Discussionmentioning
confidence: 97%
“…In three of 5 facilities, initial evacuation significantly elevated mortality after the disaster 3) . Results of previous studies 1,3) are consistent with our data.…”
Section: Discussionmentioning
confidence: 97%
“…22 Of those who were made to evacuate, more than 70 000 are still subject to a range of evacuation measures as of 5 September 2015, following slight lifts of the instructions. 23 Yasumura et al 24 and Nomura et al 25 reported threefold increase in mortality among evacuated nursing home residents up to 1 year following the incident. Elevated values of metabolic markers, including body mass index (BMI), blood pressure, glucose metabolism, lipid metabolism and liver function, were also demonstrated in evacuees, by Satoh et al 26 and Tsubokura et al, 27 1 year after the incident, suggesting worsening chronic health conditions.…”
Section: Introductionmentioning
confidence: 97%
“…For instance, the blanket evacuation technique caused a dramatically acute increase in mortality among residents of elderly nursing homes in the Fukushima area[4]. Moreover, evacuation could have long-term adverse health effects; prolonged life as evacuees could represent physical, mental and socioeconomic burdens[5].…”
Section: Introductionmentioning
confidence: 99%